THE VALUE OF DIGITAL SPACE IMAGES IN THE INTERPRETATION OF THE GISSAR DEPTH FAULT - Zokirov OtabekTolibjonovich,Tulyaganova Nargiza Shermatovna, Dulabova Nafisa Yusupovna, Ilyasova Dilfuza Makhamatsobirovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In article it is given the results of researches by different methods of digital satellite acquisition widely now in use in Uzbekistan for detection of the covered tectonic structures. New data is obtained on stretch, width and a nonconventional trajectory of the Gissarsky deep fault which is stretching on the opened and closed Chakylkalyan-Karatyube zones and Zirabulak-Ziyaetdinskymountains.